REFLEKSI PERUBAHAN SOSIAL MASYARAKAT PERKOTAAN DI INDONESIA DALAM IKLAN DI MEDIA CETAK PERIODE 1990 – 2000 - Petrus Gogor Bangsa (DeKaVe, 2011)
A modern industrialist society is an ideal society from economic growth theory by W.W. Rostow. Indonesia during the New Order government applied this theory to a program called Pembangunan Lima Tahun (Five Years Development). As the same as economic growth theory, the New Order's program also had a modern, autonomic and prosperous society as an ideal society. Even this program did not complete properly, brought a wealthy society in a part of the urban society as a positive result. This change, had influenced the urban society's lifestyle. In major of urban society, wealth is a one motive to have a hedonist lifestyle. Advertising as the component of marketing had an important part in the industrial process. In order to do its persuasive function, sometimes advertising creative applied urban lifestyle approach to got consumers interest. In the other hand, urban lifestyle could be identified through print ads visualization.Keyword : Social Change, Indonesian Tone, and Printer Ad